STUDENTS' LEARNING MOTIVATION IN BLENDED LEARNING IN ENGLISH EDUCATION STUDY PROGRAM OF UNIVERSITAS BANDAR LAMPUNG - Dewi Retno Sari; Dameria Magdalena Sidabalok (Universitas Bandar Lampung, 2022)
The objective of this study is to analyze the students learning motivation when they experience blended learning. Researchers only focus on clarifying student motivation when using blended learning system and the factors of blended learning affect motivation at third semester of English Study Program Faculty of Teacher Training and Education Universitas Bandar Lampung. This research used case study method. The research was done at English Education Study Program Faculty of Teacher Training and Education Universitas Bandar Lampung consisisted of forty six students. Data gathering was done by doing questionnaire and interview. The data was analyzed by combining the result from the questionnaire and interview. The result of this research showed that learning with the blended learning system can motivate students learning. The combination of both instruments is that blended learning system helps them to motivating in learning. They mostly agreed that this learning system could make them more interested in learning.